PENGEMBANGAN KEAHLIAN WIRAUSAHA UNTUK SANTRI PADA PONDOK PESANTREN - Bayu Sudrajat (Universitas Nahdlatul Ulama Al Ghazali Cilacap, 2022)
Islamic boarding school is one of the Islamic educational institutions in Indonesia. The reform and reconstruction of the Islamic educational system and its institutions must be carried out, especially in view of the development of the global world, which requires the constant improvement of all Islamic educational institutions. One way to increase the functionality of Islamic boarding schools concerns the financial independence of Islamic boarding schools, especially for students. Because there are still many public perceptions that students in the entrepreneurial world do not have a positive enough image. Another problem is the fate of the santri after their